BOND-SELECTED REACTION OF HOD WITH H-ATOMS - Clary, D (1992)
Calculations of vibrationally state-selected cross sections are reported for the H+HOD→H2+OD reaction. A quantum-mechanical method is used which involves a close-coupling expansion in all three vibrational modes of HOD. It is found that initial vibrational excitation of the OH bond in HOD enhances the reaction much more than excitation of the OD bond. The distributions of vibrational states in the H2+OD products are found to be closely correlated with the degree of vibrational excitation in the HOD reactant. © 1992.